Age associated axonal features in HNPP with 17p11.2 deletion in Japan. Issue 8 (15th July 2005) - Koike, H; Hirayama, M; Yamamoto, M; Ito, H; Hattori, N; Umehara, F; Arimura, K; Ikeda, S; Ando, Y; Nakazato, M; Kaji, R; Hayasaka, K; et al.
Abstract : Objective: To clarify age related changes in the clinicopathological features of hereditary neuropathy with liability to pressure palsy (HNPP) in Japanese patients with deletion of 17p11.2, particularly concerning axonal abnormalities. Methods: Forty eight proband patients from 48 HNPP families were assessed as to clinical, electrophysiological, and histopathological features, including age associated changes beyond those in controls. Results: Motor conduction studies showed age associated deterioration of compound muscle action potentials in nerves vulnerable to repetitive compression (median, ulnar, and peroneal nerves), but not in others such as the tibial nerve. Sensory conduction studies revealed more profound reduction of action potentials than motor studies with little age related change. Large myelinated fibre loss was seen in the sural nerve irrespective of age at examination. Conclusions: Irreversible axonal damage may occur at entrapment sites in motor nerves in HNPP patients, progressing with aging. Sensory nerves may show more profound axonal abnormality, but without age association. The electrophysiological features of HNPP are presumed to be a mixture of abnormalities occurring from early in life and acquired features caused by repetitive insults at entrapment sites. Unlike Charcot-Marie-Tooth disease type 1A, age associated axonal damage may not occur unless the nerves are subjected to compression.